Composting device - WANG LUJUN; WANG LANLAN; ZHANG XINGHUA; GAO JIAOJIAO; YANG XIEDING; YANG BAOYU (2014)
A composting device comprises a dewaterer, wherein the dewaterer is communicated with a mixing stirrer; the mixing stirrer is connected with a composting bin; the composting bin is connected with a secondary fermentation bin; organic solid dewatered by the dewaterer is proportioned according to carbon nitrogen ratio and moisture content required by compost and then mixed and stirred in the mixing stirrer; the mixed and stirred organic solid material is conveyed to the composting bin to be subjected to aerobic decomposition and then the treated material is heated, preserved at high temperature and finally cooled to enable the compost temperature to rise to 55 to 60 DEG C for sterilization for 8 to 12 d; the aerobic decomposed material is then conveyed to the secondary fermentation bin to ferment so as to further decompose organic substances resistant to decomposition; finally fermented grog is obtained after the completion of secondary fermentation 13 to 16 d later. The composting device has the characteristic